2013
DOI: 10.1113/jphysiol.2013.259226
|View full text |Cite
|
Sign up to set email alerts
|

Submaximal ADP‐stimulated respiration is impaired in ZDF rats and recovered by resveratrol

Abstract: Key points• Disparity exists within the literature surrounding mitochondrial dysfunction and insulin resistance and previous reports have primarily examined mitochondrial function as a capacity measurement.• We show that submaximal ADP-stimulated respiration rates are lower in ZDF rats, which coincides with decreased adenine nucleotide translocase 2 (ANT2) protein content.• Supplementation of ZDF rats with resveratrol improves skeletal muscle insulin sensitivity, increases submaximal ADP-stimulated respiration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 53 publications
1
40
0
Order By: Relevance
“…Digitonin (8.1 μmol/L) was added to the chambers to permeabilize the cells, and the assay was initiated after a 5-min incubation period. Permeabilized skeletal muscle fibers and epididymal adipose tissue were prepared as previously described (31,32). BAT mitochondria were isolated, and respiration was performed similar to previous reports (33,34).…”
Section: Respiration Methodsmentioning
confidence: 99%
“…Digitonin (8.1 μmol/L) was added to the chambers to permeabilize the cells, and the assay was initiated after a 5-min incubation period. Permeabilized skeletal muscle fibers and epididymal adipose tissue were prepared as previously described (31,32). BAT mitochondria were isolated, and respiration was performed similar to previous reports (33,34).…”
Section: Respiration Methodsmentioning
confidence: 99%
“…) and a reduction in ANT protein has been associated with impairments in submaximal ADP sensitivity and oxidative stress (Smith et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…Comparable behaviour was reported for mitochondria isolated from the hearts of STZ-induced diabetic rats by Pierce and Dhalla [63]. Since those early studies, functional impairment of diabetic cardiac mitochondria has been reported in a variety of animal models: genetically diabetic mice [64], STZ-induced type 1 diabetic rats [65], insulin-resistant and obese mice [43,44] and Zucker Diabetic Fatty rats at submaximal rates of ADP-stimulated respiration [66], even prior to the development of symptoms of diabetic cardiomyopathy [67]. Our recent (unpublished) results (Figure 3) are in general accord.…”
Section: Evidence From the Literaturementioning
confidence: 70%